Low‐density lipoprotein cholesterol lowering in real‐world patients treated with evolocumab. Issue 5 (24th March 2021) - Desai, Nihar R.; Wade, Rolin L.; Xiang, Pin; Pinto, Lionel; Nunna, Sasikiran; Wang, Xin; Exter, Jason; Mues, Katherine E.; Habib, Mohdhar; Chen, Chi‐Chang
Abstract: Background: Low‐density lipoprotein cholesterol (LDL‐C) is a risk factor for atherosclerotic cardiovascular disease (ASCVD). There are limited real‐world data on LDL‐C lowering with evolocumab in United States clinical practice. Hypothesis: We assessed LDL‐C lowering during 1 year of evolocumab therapy. Methods: This retrospective cohort study used linked laboratory (Prognos) and medical claims (IQVIA Dx/LRx and PharMetrics Plus ® ) data. Patients with a first fill for evolocumab between 7/1/2015 and 10/31/2019 (index event) and LDL‐C ≥ 70 mg/dL were included (overall cohort; N = 5897). Additionally, a patient subgroup with a recent myocardial infarction (MI) within 12 months (median 130 days) before the first evolocumab fill was identified (N = 152). Reduction from baseline LDL‐C was calculated based on the lowest LDL‐C value recorded during a 12‐month follow‐up period. Results: The mean (SD) age was 65 (10) years; 61.9% of patients had ASCVD diagnoses and 70.7% of patients were in receipt of lipid‐lowering therapy. Following evolocumab treatment, changes in LDL‐C from baseline were −60% in the overall cohort (median [interquartile range (IQR)] 146 [115–180] mg/dL to 58 [36–84] mg/dL) and −65% in the recent MI subgroup (median [IQR] 137 [109–165] mg/dL to 48 [30–78] mg/dL). In the overall cohort and recent MI subgroup, 62.1% and 69.7% of patients achieved LDL‐C < 70 mg/dL, respectively. Conclusions: In this real‐world analysis, evolocumab was associated with significant reductions in LDL‐C comparable to that seen in the FOURIER clinical trial, which were durable over 1 year of treatment.